Developing SMS Content to Promote Papanicolaou Triage Among Women Who Performed HPV Self-collection Test: Qualitative Study - Kohler, Racquel E (2020)
Fil: Kohler, Racquel E. Cancer Health Equity, Cancer Institute of New Jersey, Rutgers, The State University of New Jersey; Estados Unidos.